Sifat Anti Jamur dari Ekstrak Biji Pinang (Areca cathecu) dan Daun Saga (Abrus precatorius) - Anis S. Lestari; Titik Kartika; Deni Zulfiana; Maya Ismayati Maya Ismayati (Masyarakat Peneliti Kayu Indonesia, 2010)
This research purposed to define effect of Pinang (Areca cathecu) seed and Saga (Abrus precatorius) leaf extract against wood decay fungi (Trametes versicolor and Fomitopsis palustris). To obtain active compounds, saga leaf and seed of pinang were extracted with methanol and evaporated by vacuum evaporator. To conduct antifungal test, PDA medium that had been mixed with crude extract of pinang or saga by comparison of 1:1 (w/v) was used. The examination fungal growth was based on its radius colony was conducted for 8 days. Saga leaf extract has higher antifungal activity against T. versicolor and F. palustris than pinang seed extract. Inhibition percentage of fungal growth by saga leaf extract achieved 100%. Based on this research, pinang and saga could be recommended forfurther research as one of biological controlagent.